Peningkatan Kompetensi Sumber Daya Manusia dalam Pengajaran : Pelatihan Aplikasi Canva untuk Meningkatkan Kreativitas Guru Sekolah Dasar Negeri Basirih 11 - Abdurrahim Abdurrahim; Jumiati Jumiati; Mahmudin Mahmudin; Mahfuz Afif Maulana; Rasisca Tita Marvelia; Agnia Aslam (Institut Teknologi dan Bisnis Semarang, 2025)
The use of technology in education is increasingly important, especially at the Elementary School (SD) level, to improve the quality of teaching and learning. Along with the rapid development of technology, teachers are required to be able to utilize various applications that support the teaching process, one of which is the Canva graphic design application. This article discusses training in the use of the Canva application for teachers at SDN Basirih 11, with the aim of improving teacher competence in utilizing technology in teaching. This training aims to improve teachers' ability to use Canva to create more creative, interesting, and interactive teaching materials, as well as introduce the concept of technology-based learning management. The method used in this training combines theoretical and practical approaches, with a focus on improving technical skills and creativity. The results of this training show an increase in teachers' technical abilities in using Canva, increased creativity in compiling teaching materials, and increased understanding of the importance of technology in learning management. This training is expected to encourage teachers to be more active in utilizing technology, especially in creating interesting learning media, which can improve the quality of education in Elementary Schools.